Pengaruh Bakteri Bacillus Megaterium Sebagai Self-Healing Agent Pada Kuat Tekan Beton Dengan Agregat Buatan Berbasis Limbah Fly Ash - Fikkry Agustiansyah; Raya Syah Adzani; Luthfi Muhammad Mauludin; Linda Aisyah (Jurnal Konstruksi dan Infrastruktur : Teknik Sipil dan Perencanaan, 2025)
In the construction world, there exist an innovation to make use of artifical aggregates to reduce using natural aggregates that are limited in nature, but their usage usually lowers the concrete’s compression strength. That is why the innovation of utilizing bacteria as a healing agent can be used for its self-healing property to fix cracks formed on the concrete. In this study, the bacteria bacillus megaterium were used as a healing agent with a percentage of 2% of the composition of the water used and artifical aggregate with the optimal composition of 60% type F fly ash : 40% of the inorganic compound calcium hydroxide with a water content of 37,7% of the weight of fly ash used. The artifical aggregate is made using the pan granulator method and water is sprayed evenly during its production. The compression test of the concrete is done with samples at the size of 100 x 200 mm and 150 x 300 mm on 28 days of age. In this study, 4 variables of fly ash are compared which are 100%, 100% with 2% bacteria, 50% with 2% bacteria, and normal concrete. The compression strength results at 28 days of age in order are 15,27 MPa, 22,16 MPa, 21,57 MPa, and 22,61 MPa. After 30 days of healing, the average compressive strengths of the specimens were 11,8 MPa, 14,45 MPa, 27,33 MPa, and 12,6 MPa, with healing efficiencies of 58,58%, 67,72%, 123,33%, and 48,08%, respectively.